Beneficial arthropods threatened by synthetic agricultural pesticides around the southeast slopes of Mount Cameroon - Daniel Brice Nkontcheu Kenko; Agathe Lambou Fotio; Kenfack Donhachi Aimerance; Derick Atemlefac Acha; Miranda Egbe Awo; Eric Bertrand Fokam (Heliyon)
Agriculture is among the main drivers of global biodiversity decline. This research assessed the ecological risk of synthetic pesticides at the southeast slopes of Mount Cameroon on bees and other non-target arthropods (NTAs) using the PRIMET (Pesticide RIsk in the tropics to Man, Environment and Trade) model. Data on pesticide usage (active ingredients, interval, dosage, number of applications), and ecotoxicology (LD50 and environmental behaviour) were collected from field surveys and the IUPAC databases, respectively, then imported into PRIMET to assess the level of risk expressed in Exposure Toxicity Ratio (ETR). Tomato was the main crop of the area while insecticides were the main pesticide category utilised in the study area. Nine (09) compounds were predicted to pose a “risk” to bees namely abamectin, fipronil, imidacloprid, thiamethoxam, emamectin-benzoate, cypermethrin, lambda-cyhalothrin, indoxacarb and ethoprophos. Abamectin had the highest ETR in the group (NECbee = 0.05 g a.i./ha; ETRbee = 20000). Fifteen (15) active ingredients were predicted by the model to pose a certain in-field risk to NTAs with lambda-cyhalothrin at the top position (AECNTA = 0.0034 g a.i./ha; ETRIF = 1147000). There was evidence that insecticides were of more risk to beneficial arthropods, as compared to other types of pesticides. Pesticides active ingredients such as abamectin, fipronil, imidacloprid, thiamethoxam, emamectin-benzoate, cypermethrin and lambda-cyhalothrin that were predicted to pose “Risk” both to bees and others NTAs require serious mitigation strategies (biological control, improve cultural practices, target application, farmer's education).